Efficiency Gain from Ownership Deregulation: Estimates for the Radio Industry. - Smith, H; O’Gorman, C (Department of Economics (University of Oxford), 2008)
Reducing …fixed cost duplication - a common justi…cation for concentrated market structure - motivated the US government to relax the number of radio stations a …firm could operate in any local market. After deregulation the number of fi…rms per market decreased. The implied cost saving depends on the per market …fixed costs incurred by each fi…rm. Using data from 140 markets we estimate upper and lower bounds to fixed costs using (i) an empirical model of gross pro…fit and (ii) the assumption that the observed post-deregulation market structure is a Nash equilibrium. The estimates suggest that the efficiency savings were signi…cant.